2011
DOI: 10.1111/j.1440-1843.2011.02021.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin‐13 C‐1112T and G+2044A polymorphisms with asthma: A meta‐analysis

Abstract: This meta-analysis indicated that the IL13 C-1112T and G+2044A polymorphisms predispose to asthma. Further studies, including pooling of individual data to facilitate evaluation of gene-gene and gene-environment interactions between these IL13 gene polymorphisms and asthma susceptibility, are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
(132 reference statements)
0
13
0
Order By: Relevance
“…8,9 The IL-13 gene is found on chromosome 5q31-33 and has been significantly associated with allergic asthma. 10 The T allele of the IL13 C1923T and IL13 C1112T have both shown to be significantly associated with increased risk of asthma, 11,12 and rs1295686 is involved in the dysregulation of total IgE.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The IL-13 gene is found on chromosome 5q31-33 and has been significantly associated with allergic asthma. 10 The T allele of the IL13 C1923T and IL13 C1112T have both shown to be significantly associated with increased risk of asthma, 11,12 and rs1295686 is involved in the dysregulation of total IgE.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis performed by Yang et al [41] found +2044A/G polymorphism was associated asthma risk in Asians but not in Caucasians. Another meta-analysis conducted by Cui et al [42] showed this polymorphism was more pronounced among Caucasians but not among Asians.…”
Section: Discussionmentioning
confidence: 95%
“…There are several potential explanations for the different results. First, different inclusion and exclusion criteria were used in these two meta-analyses [41], [42]. For example, Cui et al [42] only included English papers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations